DESAIN KEBIJAKAN PEMASARAN SOSIS DAGING AYAM EDIBLE CASING MENUJU INDUSTRI 4.0 DENGAN MENGGUNAKAN INTERPRETATIVE STRUCTURAL MODELLING - Rosmawaty AN; Tini Sabrina Pratamaningtyas; Aji Jumiono (Jurnal Governansi, 2022)
Consumption of breakfast sausage by people of Indonesia has increased about 4.46% per year. Kind of consumed breakfast sausage is chicken breakfast sausage. This research aims to design the marketing policy of edible casing chicken breakfast sausage toward industry 4.0. Design of marketing policy is based on six key elements, namely purpose, product, obstacle, institution, marketing, and technology. Method of this research uses Interpretative Structural Modelling (ISM) supported by Software ISM Profesional 2.0. Results of this research indicate that the design of marketing policy of edible casing chicken breakfast sausage toward industry 4.0 is based on six following key elements. (1) Element of purpose emphasizes the fulfilment of marketing authorization requirement and halal certification. (2) Element of product emphasizes the labelled package in accordance with the marketing authorization and the impressively-labelled package. (3) Element of obstacle emphasizes the preparation of skilled human resource. (4) Element of institution emphasizes the National Agency of Drug and Food Control as authority that issues marketing authorization and the Ministry of Religion as authority that issues halal certification. (5) Element of marketing emphasizes the marketing system of online advertisement and the advertisement system of electronic media. (6) Element of technology emphasizes the preparation of online data storage system.